3‐(Diphenylphosphino)propanoic acid: an efficient ligand for the Pd/Cu‐catalyzed homo‐coupling of terminal alkynes in the presence of oxygen at room temperature. (6th August 2015) - Liu, Yashuai; Gu, Ningning; Liu, Ping; Xie, Jianwei; Ma, Xiaowei; Liu, Yan; Dai, Bin
Abstract : A simple, yet efficient system for PdCl2 /CuI to catalyze the homo‐coupling reactions of various terminal alkynes has been developed using 3‐(diphenylphosphino)propanoic acid as ligand in the presence of oxygen. The alkynes, including aromatic, heteroaromatic and aliphatic alkynes, were transformed at room temperature into the corresponding 1, 3‐diynes in moderate to excellent yields. The turnover number was up to 1.04 × 10 3 . Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Alkynes, including aromatic, heteroaromatic and aliphatic alkynes, were transformed at room temperature into the corresponding 1, 3‐diynes in good yields using PdCl2 /CuI to catalyze the homo‐coupling reactions using 3‐(diphenylphosphino) propanoic acid as ligand in the presence of oxygen.